2018
DOI: 10.2169/internalmedicine.0923-18
|View full text |Cite
|
Sign up to set email alerts
|

Osimertinib Treatment Was Unsuccessful for Lung Adenocarcinoma with G719S, S768I, and T790M Mutations

Abstract: Abstract:Epidermal growth factor receptor (EGFR) T790M mutations are the most frequent mechanism of resistance to first-and second-generation tyrosine kinase inhibitors, and osimertinib is an effective treatment for patients with both EGFR-activating mutations and T790M resistance mutations. We describe the case of a 68-year-old woman with lung adenocarcinoma with G719S, S768I, and T790M mutations in which osimertinib treatment was unsuccessful. The patient died of disease progression one month after discontin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
(11 reference statements)
2
5
0
Order By: Relevance
“…Consistent with our study, AURA study observed a relatively lower response rate in patients harboring uncommon sensitive EGFR mutation when comparing with these harboring 19del/L858R [43]. Similarly, several cases found the inferior efficacy of osimertinib in patients harboring uncommon mutations after progression on prior EGFR-TKIs, even in patients with positive T790M mutation [44][45][46], suggesting an alternative more potent anti-cancer strategy is needed for this setting.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with our study, AURA study observed a relatively lower response rate in patients harboring uncommon sensitive EGFR mutation when comparing with these harboring 19del/L858R [43]. Similarly, several cases found the inferior efficacy of osimertinib in patients harboring uncommon mutations after progression on prior EGFR-TKIs, even in patients with positive T790M mutation [44][45][46], suggesting an alternative more potent anti-cancer strategy is needed for this setting.…”
Section: Discussionsupporting
confidence: 88%
“…In clinical course and response to osimertinib, our case was similar to the previous case reported by Nasu et al, in which osimertinib was unsuccessful for emergence of the same combination of mutations after gefitinib, erlotinib and afatinib [7]. The main lesions were the progression of primary tumor and pleural effusion and the emergence of brain metastases in the previous case [7], while our case presented with the rapid progression of multiple liver metastases and the sudden emergence of Trousseau syndrome. These two cases suggested that acquired S768I may be refractory to osimertinib and accelerate rapid progression, even if it occurs together with T790M.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, among the seven NSCLC patients with G719X mutations included in the AURA trial for second-line osimertinib, only one (RR = 14%) showed partial response (PR), three (43%) had SD, and three (43%) displayed progressive disease (PD) [93]. In keeping with that, lack of response to osimertinib and immediate progression have been described in a patient with G719S/T790M co-mutations [92] and another one with co-existing G719S, S768I, and T790M mutations [94]. Collectively, these data seem to indicate that osimertinib, as opposed to afatinib, is less effective in patients with EGFR G719X and other uncommon mutations than in those with classic EGFR -mutants, both in the presence and absence of T790M co-mutation.…”
Section: Clinical and Preclinical Studies Shedding Light On Intrinmentioning
confidence: 91%